Study of anatomical structures contours in problems of morphometric analysis - Аврунін, О. Г.; Тимкович, М. Ю.; Дуденко, В. Г.; Кононенко, Т. С.; Avrunin, O. G. (Deutscher Wissenschaftsherold, 2016)
The work deals with the contours of anatomical structures, namely, the lateral ventricles of the brain. We have analyzed the contours of the lateral ventricles at different horizontal sections of tomographic images. We have shown the possibility and the need to use geometric data of these structures geometry while analysing tomographic images.
Keywords: computed tomography; brain; contour analysis; lateral ventricles